Smartphone Privacy. Finnish young people's perceptions of privacy regarding data collected when using their mobile devices - Mäkinen Liisa A.; Junnila Johanna (Nordicom, 2025)
In this chapter, we explore Finnish teenagers’ experiences and understandings of privacy concerning the data stored in and flowing through their smartphones. Building mostly on qualitative interview data collected in Finland, we investigate what kind of factors are meaningful for young people when thinking about privacy on mobile devices, and how the level and nature of privacy required depends on the audience. Our results reveal that banking information, passwords, fingerprints, and locations were considered the most private information on smartphones. A myriad of personal factors affected how certain information was deemed more private than other kinds, hinting that much of this judgement lies in the context. Privacy matters to young people, but it seems to hold more meaning in social contexts and often remains overlooked in institutional settings, where the potential risks of privacy losses may seem unclear, abstract, or even irrelevant.
Everyday life in the culture of surveillance